Trains of Neural Thought. - Milner, Peter M. (Canadian Psychology, 2006)
The neural implementation of concepts as postulated by Hebb (1949), has become obsolete due to the advances in neuroscience during the last half-century, but the basic idea revolutionized psychology and remains valuable. This paper charts changes chat have been imposed on Hebb's cell assembly by our greater understanding of the anatomy and neurophysiology of the visual system and our better recognition of the influence of “top-down” attention on perception. Difficulties encountered in trying to find neural explanations for the association of ideas are also discussed. La mise en œuvre neurale des concepts, telle que précon-isé par Hebb (1919), est devenue obsoléte en rasion des progrés en neuroscience an cours de la derniére moitié du siécle dernier, mais l'idée fondamentale a révolutonné la psychologie et demeure tout, à fail intéressante. Get article trace les changements qui out été imposés à la notion d'assemblée cellulaire de Hebb par none plus grande comprehénsion de I'anatomie et de la neurophysiologie du systéme visuel et notre meilleure reconnaissance des mécanisines d'attention de type “top-down” sur la perception. Les difficultes rencontrées en essayant de trouver des explications neurales de I'association des idéees fout également I'objet de discussion. Reprinted by permission of the publisher.